2015
DOI: 10.1097/opx.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Discomfort Responses after Short Periods of Contact Lens Wear

Abstract: Short periods of wear can be experienced at any time of day without significant change in ocular discomfort and dryness. This suggests that subjective responses at the end of the day are determined by the length of time lenses are in contact with the eye, rather than the time of day at which lenses are worn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…In addition, every subject in the cohort reported good comfort and dryness with SLs, and their subjective ratings were comparable with ratings of soft contact lens wear. 18,19 Therefore, we conclude that post-lens tear mixing is slow during scleral lens wear, as the changes of bulbar and limbal redness, and corneal staining and average comfort score after 5-hour scleral lens wear, were comparable with published data for soft contact lens wear. 20,21 This finding may be different with other lens designs and especially in the light of the emergent trend of customizing the scleral lens fit with toric peripheries.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, every subject in the cohort reported good comfort and dryness with SLs, and their subjective ratings were comparable with ratings of soft contact lens wear. 18,19 Therefore, we conclude that post-lens tear mixing is slow during scleral lens wear, as the changes of bulbar and limbal redness, and corneal staining and average comfort score after 5-hour scleral lens wear, were comparable with published data for soft contact lens wear. 20,21 This finding may be different with other lens designs and especially in the light of the emergent trend of customizing the scleral lens fit with toric peripheries.…”
Section: Discussionsupporting
confidence: 85%
“…In order to establish whether CLD is a function of the time of day at which lenses are worn, Papas et al assessed comfort in a group of participants without lens wear over an 8-h period and showed that this stayed reasonably constant throughout the observation period. 76 When participants were fitted with contact lenses for 12 h, after the first few hours, comfort scores reduced significantly, in a fashion typical of that commonly expressed by contact lens wearers. When participants were asked to wear the contact lenses for 4-h periods starting in the morning, in the afternoon, or late afternoon, a characteristic pattern resulted, regardless of the starting point.…”
Section: The Clinical Signs Of Cldmentioning
confidence: 88%
“…Thus, analyzing the safety and comfort of silicone hydrogel SCL it can be noted that the probability of DES development is considered against the background of their use in the majority of researches [8,9]. However, the dynamic research of the clinical picture of the dry eye having developed after systematic use of SCL according to clinical recommendations is undoubtedly important [13]. A topical issue is the comprehensive assessment of functional parameters reflecting lacrimation and tear film stability during the development of pathological process.…”
Section: Problem Statement and Analysis Of The Recent Researchmentioning
confidence: 99%